Pengaruh Daya Tarik dan Fasilitas terhadap Minat Berkunjung Kembali - Rosta Juliana Sinaga; Tengku Teviana (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This research was conducted to find out whether there is an influence of attraction and facilities on interest in returning to Sipinsur Geosite Tourism. This research used quantitative methods, the population in this study was 252,601 people. Data processing uses the SPSS 20 program. The results of the research show that: (1) partial attractiveness has a positive and significant influence of 19.7% on interest in returning to visit, (2) partial facilities have a positive and significant influence of 63.5% on interest in returning to visit, (3) Attraction and facilities together have a positive and significant influence on interest in returning to visit. The adjusted coefficient of determination (Adjused R2) is 0.821, which means that the variables Attraction and Facilities are able to contribute to the influence of interest in returning to visit by 82.1% while the remaining 17.9% is determined by other variables outside this research model. This shows that there are still other variables that explain Intention to Revisit.